Consumer Gratification Regarding Insurance Companies: A Case Study of Shimla (International Journal of Innovative Research in Engineering & Management, 2021)
In India, the life insurance industry has seen significant  development in recent years. Insurance services are undergoing a  transformation, and the industry's openness has posed many  serious risks and difficulties to Life Insurance Corporation of  India (LIC), the country's sole public sector life insurance service  provider. People are worried about their own and their loved one’s futures. Life insurance provides assistance to a deserving  recipient at a difficult period. Life insurance firms, on the other  hand, are in fierce rivalry. Players in the life insurance industry  have begun to recognize that customer service and satisfaction are  critical to their success. As a result, a proactive approach to client  satisfaction should be taken. The effect of demographic variables  on customer satisfaction with Life Insurance Company is  investigated in this research. It was shown that most policyholders  consider their life insurance company to be safe and reliable. It is  recommended that a life insurance company offer timely and  accurate information to current clients in order for them to remain  loyal and promote good word of mouth about them.
Keywords: Consumer Contentment Consumer Gratification; Customer Satisfaction; Endowment; Life Insurance; Insurance Policy